Association of Other Autoimmune Diseases With Thyroid Eye Disease - Kelada, Mary; Avari, Parizad; Farag, Soma; Akishar, Rashmi; Jain, Rajni; Aziz, Ahmad; Feeney, Claire; Bravis, Vassiliki; Meeran, Karim; Lee, Vickie (Frontiers in Endocrinology, 2021)
Background: Thyroid eye disease (TED) is a potentially disfiguring and sight-threatening autoimmune (AI) orbitopathy, affecting up to 400,000 people in the UK. There are no accurate early predictors of TED severity. Although polyautoimmunity has been shown to affect AI disease severity, its influence on TED severity has never been investigated. The prevalence of polyautoimmunity among TED patients is also unclear, with discordant results reported in the literature. This study evaluates the prevalence of non-thyroid/ ‘other’ AI (OAI) conditions in an ethnically diverse TED cohort and assesses how polyautoimmunity affects TED severity and activity. Methods: A retrospective study of patients presenting to multidisciplinary TED clinics across three North-West London hospitals between 2011-2019. Data collected included: 1) demographics; 2) OAI conditions and management; 3) endocrine management of thyroid dysfunction; 4) details of TED and clinical activity score at presentation. Results: 267 patients with a median age of 46 (35-54) years were included, 79.4% were female and 55% were Black, Asian and minority ethic (BAME). Thirty-seven patients (13.9%) had OAI conditions, with rheumatoid arthritis (3.7%), vitiligo (3.0%) and psoriasis (3.0%) among the most prevalent. Of patients with OAI conditions, 43.2% (16/37) required immunosuppression prior to TED onset. Non-immunosuppressed patients with OAI conditions had a significantly higher clinical activity score at presentation than TED-only and previously immunosuppressed patients (p=0.02). No significant differences were observed in thyroid receptor antibody titres between these groups. Conclusions: This study finds a 13.9% prevalence of OAI conditions among TED patients. Patients with OAI conditions overall have a tendency for more severe and significantly more clinically active TED than those without OAI conditions. Larger, prospective studies are warranted to further evaluate polyautoimmunity as an early predictor of TED severity.